PENGEMBANGAN KEPEMIMPINAN DALAM PENDIDIKAN ISLAM: TINJAUAN KONSEPTUAL DAN IMPLEMENTATIF DI LEMBAGA PENDIDIKAN ISLAM KONTEMPORER - Saputri Kelana; Junaidi (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
The development of leadership in Islamic education is a strategic issue that continues to evolve in line with the dynamic needs of Islamic educational institutions in the contemporary era. The challenges of globalization, technological advancement, and shifts in socio-cultural values require Islamic educational institutions to have leaders who are not only technically and managerially competent, but also morally and spiritually strong. This article aims to comprehensively and conceptually examine how leadership can be developed in the context of Islamic education through the integration of prophetic, transformational, and managerial values. This study uses an in-depth literature review approach by analyzing various recent studies on leadership in Islamic educational institutions, including schools, madrasahs, and pesantrens. The results show that the development of leadership in Islamic education must be grounded in the values of the Quran and Sunnah, while also accommodating the demands of 21st-century skills. The most relevant leadership model is transformational-prophetic leadership that is able to harmoniously integrate spiritual, intellectual, and managerial dimensions. The conclusion of this study affirms that effective Islamic education leaders are those who are able to holistically develop their own competencies, empower human resources, create an organizational culture based on Islamic values, and respond wisely to the changing times. ABSTRAK Pengembangan kepemimpinan dalam pendidikan Islam merupakan isu strategis yang terus berkembang seiring dengan dinamika kebutuhan lembaga pendidikan Islam di era kontemporer. Tantangan globalisasi, kemajuan teknologi, dan pergeseran nilai-nilai sosial-budaya menuntut lembaga pendidikan Islam untuk memiliki pemimpin yang tidak hanya kompeten secara teknis-manajerial, tetapi juga kuat secara moral dan spiritual. Artikel ini bertujuan untuk mengkaji secara konseptual dan komprehensif bagaimana kepemimpinan dapat dikembangkan dalam konteks pendidikan Islam melalui integrasi nilai-nilai profetik, transformasional, dan manajerial. Kajian ini menggunakan pendekatan studi literatur mendalam dengan menganalisis berbagai penelitian terkini mengenai kepemimpinan di lembaga pendidikan Islam, mencakup sekolah, madrasah, dan pesantren. Hasil kajian menunjukkan bahwa pengembangan kepemimpinan dalam pendidikan Islam harus berpijak pada nilai-nilai Al-Qur'an dan Sunnah, sekaligus mengakomodasi tuntutan keterampilan abad ke-21. Model kepemimpinan yang paling relevan adalah kepemimpinan transformasional-profetik yang mampu mengintegrasikan dimensi spiritual, intelektual, dan manajerial secara harmonis. Simpulan kajian ini menegaskan bahwa pemimpin pendidikan Islam yang efektif adalah mereka yang mampu mengembangkan kompetensi diri secara holistik, memberdayakan sumber daya manusia, menciptakan budaya organisasi yang berlandaskan nilai-nilai Islam, serta merespons perubahan zaman dengan bijaksana.